2020
DOI: 10.3390/jcm9041213
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Glucose Utilization Contributes to Memory Impairment in Patients with Glufosinate Ammonium Intoxication

Abstract: The symptoms of glufosinate ammonium (GLA) intoxication include gastrointestinal and neurologic symptoms, respiratory failure, and cardiovascular instability. Among these, neurologic symptoms including loss of consciousness, memory impairment, and seizure are characteristic of GLA poisoning. However, the mechanism of brain injury by GLA poisoning is still poorly understood. We investigated nine patients who had performed an F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET) scan because of memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The exact mechanism of respiratory failure in glufosinate poisoning has not been fully revealed. We previously reported that brain glucose metabolism decreased in patients with glufosinate intoxication [28]. Also, Park et al reported that the inhibition of both glycolysis and mitochondrial respiration pathway might be associated with oxidative stress and ferroptosis in human astrocytes [29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The exact mechanism of respiratory failure in glufosinate poisoning has not been fully revealed. We previously reported that brain glucose metabolism decreased in patients with glufosinate intoxication [28]. Also, Park et al reported that the inhibition of both glycolysis and mitochondrial respiration pathway might be associated with oxidative stress and ferroptosis in human astrocytes [29].…”
Section: Discussionmentioning
confidence: 95%
“…Also, Park et al reported that the inhibition of both glycolysis and mitochondrial respiration pathway might be associated with oxidative stress and ferroptosis in human astrocytes [29]. Given the role of astrocytes in glucose metabolism and putative mechanisms associated with glufosinate [28], respiratory failure in glufosinate intoxication might be attributed to impairment of glucose metabolism. We hope further study could reveal the mechanism of respiratory failure in glufosinate poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…The median time for consciousness and convulsion or seizure was 33.0 (26.0, 40.0) hours and 45.0 (37.5, 48.5) hours after ingesting GA, respectively. Inhibition of glutamine synthetase by glufosinate ammonium may lead to elevated blood ammonia levels that are related to neurotoxicity symptoms [15]. Glutamine synthetase is a crucial enzyme in the human body that plays a critical role in brain metabolism and the normal function of various organs [16].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that glucose hypometabolism could lead to long-lasting memory impairment regardless of structural brain lesions. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%